Study Of Prevalence Of Anxiety And its Contributing Factors Among Patients Undergoing Surgery In a Tertiary Care Hospital - Subedi, S.; Paudel, K.; Koirala, M.; Chhetri, P. (Journal of Psychiatrists’ Association of Nepal, 2019)
Introduction: Anxiety is a vague, uneasy feeling, the source of which is often non-specific but known to cause abnormal hemodynamic changes as a consequence of sympathetic, parasympathetic and endocrine stimulation. Most patients awaiting elective surgery experience anxiety. The degree, to which patient develops anxiety depends on many factors like age, gender, type and extent of the proposed surgery, previous surgical experience, and personal susceptibility to stressful situations. This study was conducted to find out the prevalence of preoperative anxiety and factors contributing to it. Material and Method: This is a cross-sectional study done among 74 pre-operative patients admitted the day before elective surgery in Department Of Surgery Universal College Of Medical Sciences Teaching Hospital, Bhairahawa. Socio-demographic as well contributing factor questionnaire, semi structured pro forma by interview method and Beck Anxiety Inventory Scale (BAI) Nepali Version were used to collect the data. Results: The findings of the study revealed that 90.54%, had very low level of anxiety and 2.70% of patients had severe pre-operative anxiety. The bivariate logistic regression analysis showed statistically significant association between family income (p= 0.004, AOR=2.03, CI= 0.009-2.567), family support (p< 0.001, AOR= 2.34, CI= 0.003-3.368), expected duration of hospital stay (p= 0.049, AOR=8.889, CI= 78.051-78.051), clarity on given information by health care providers (p< 0.001, AOR= 53.33, CI=7.165-396.99), staffs friendliness (p< 0.001, AOR= 21.01, CI= 3.450-127.82), fear of nil per oral (p= 0.015, AOR= 2.32, CI= 0.26-3.67) and level of pre-operative anxiety. Conclusion: It is concluded that varying degree of pre-operative anxiety were found in patients undergoing surgery. Providing adequate information about Peri-Operative procedure can help in reducing these anxiety.